Diálogos entre Stakeholders: O caso da cadeia produtiva do algodão orgânico - Fernandes, Milene Ovando (2021)
The production chains are changing along with the demands for new forms of production that promote sustainable practices. Among them, there is organic production that avoids the use of pesticides and contributes to the maintenance of ecosystems and the socioeconomic development of workers in the chains. However, they are subordinate to some challenges imposed by their activities and working conditions. In order to seek the mitigation of chain problems, the stakeholder dialogue is an important approach, which if carried out correctly brings numerous benefits to the chains. Thus, the objective of the research is to analyze the stakeholder dialogues in the organic cotton production chain, based on the case study of the cooperative Justa Trama. This chain is part of the organic textile sector and is made up of associations and cooperatives that make up the production links, located in several Brazilian regions. The research has a qualitative approach and the primary data collection occurred from semi-structured interviews with a stakeholder from each link of production of Justa Trama. Data analysis was based on content category analysis and verification of the adherence of the characteristics of the dialogues with the Ten Preconditions for an Effective Stakeholder Dialogue proposed by Kaptein and Tulder (2003). As a result, it was concluded that Justa Trama promotes its dialogues from assemblies, meetings and WhatsApp groups. The dialogues had characteristics that make them effective. In addition, they contribute to the emergence of learning among stakeholders and transparency in the production chain, and consequently, they drive problem solving. It was also concluded that the dialogues provide social, economic and environmental benefits to its stakeholders, thus, generate incentives for the continuity of the dialogues in the chain.